ANALISIS KINERJA PENILIK PNF DI KABUPATEN GORONTALO - Rahmat, Abdul (JIV-Jurnal Ilmiah Visi, 2011)
The role of inspectors is considered as highly strategic to helping the implementation of nonformal education in Indonesia. This research has aim to describe the inspectors’ performance in the implementation and quality control of nonformal education. With fenomologis approach, the data is collected by observation, interview, and document study. The result of this research showed that the inspector in Gorontalo not implement the entire main task and the function optimally yet. Because of that, this research suggested to increasing the competency of inspector by upgrading and another relevant forum.